The Important Role Of Human Resource Management (Hr) In Addressing The Challenges Of The Digital Era And Improving Societal Well-Being - Fadillah, Zikry Indra; Freitas, Carlos; Lopes, Clara (SABA JAYA PUBLISHER, 2024)
Human Resource Management (HRM) is pivotal in driving organizational success and societal well-being, particularly in the contemporary digital era. This paper elucidates the imperative of optimizing HRM practices to achieve maximum organizational performance and sustainable economic well-being. It explores the multifaceted aspects of HRM, including recruitment, training, performance appraisal, and compensation, emphasizing their direct impact on employee productivity and motivation, thereby influencing organizational outcomes and economic welfare. Furthermore, it delves into the challenges posed by globalization, technological advancements, and changing consumer behavior, necessitating a strategic and adaptive approach to HRM. The study underscores the importance of innovative, data-driven HRM strategies to enhance organizational performance and employee well-being. Moreover, it highlights the significance of sustainability and social responsibility in HR practices, advocating for fair, inclusive, and environmentally friendly approaches. Drawing from qualitative research methods, the paper presents insights into the role of HRM in promoting work-life balance, enhancing digital skills, and managing change in the digital era. It concludes by emphasizing the pivotal role of HRM in navigating digital challenges and fostering societal well-being, advocating for investments in HR management and digital capabilities to thrive in the digitalized world.